The genius under the table : growing up behind the Iron Curtain - Yelchin, Eugene (Candlewick Press, 2021)
Relates stories from the childhood of Eugene "Yevgeny" Yelchin, growing up in Cold War-era Russia as the author, as a young boy, attempts to learn his place in h is family and in the dangerous world he finds himself in. Much of the revelations take place beneath Yevgeny's grandmother's kitchen table, where he spent time drawing doodles which, though he didn't know it then, would help him change everything.